The girl from the other side : Siúil, a Rún. Vol. 11 - Nagabe (Seven Seas, 2021)
"In a world split between the Inside and the Outside, those living in both realms are told never to cross over to the other side, lest they be cursed. A young girl named Shiva lives on the other side, in a vacant village with a demonic guardian known only as Teacher. Although the two are forbidden to touch, they seem to share a bond that transcends their disparate appearances. But when Shiva leaves Teacher care to seek out her grandmother, the secret behind her mysterious living arrangement comes to light."--Publisher's description.